Chlorophyll a in the water column in Unguja Island (Zanzibar Archipealgo, Tanzania) sampled in 2016 - Agustín Moreira-Saporiti; Mirta Teichberg (PANGAEA, 2021)
We studied if functional traits related to resource preemption (light and inorganic nutrients) exert control on space preemption of tropical seagrass meadows. Additionally, we studied if space preemption changed under different eutrophication scenarios. We took seagrass abundance data to study space preemption, seagrass traits data to study their effect on space preemption and eutrophication indicators to evaluate the level of eutrophication at each site/sampling event. The data was collected in Unguja Island (Zanzibar Archipealgo, Tanzania) in seven sites/sampling events (Harbor, Chapwani, Changuu, Bweleo, Fumba, Mangroves and Marumbi). Each site/sampling event comprised a subtidal seagrass meadow (2-4 meters depth) of around 2500 square meters, delimited by the coastline and a fringing reef. The data was taken between the 26.09.2016 to the 05.10.2016. In each site/sampling event, five 50 meters transects were deployed perpendicular to the coast and paralel to each other, approximately separated by 50 meters. The areas enclosed beweeen the transects were names A, B, C and D. Chlorophyll a in the water column was collected as an indicator of eutrophication. In the proximities of each transect, we collected five ~3-liter seawater samples from each site/sampling event and kept them in a cooler box until filtration. Seawater was immediately filtered upon arrival in the Institute of Marine Sciences (IMS, Stone Town, Zanzibar) under constant pressure onto pre-combusted (5 h, 450°C) and pre-weighed Whatman GF/F filters (0.45 μm pore size). The filters were stored at -20°C and transported frozen to the Leibniz Centre for Tropical Marine Research in Bremen (Germany). Chlorophyll-a was extracted from the filters in 8 ml of 96% ethanol in glass vials heated for 5 min at 80°C, covered with aluminum foil, and placed in a rotor at room temperature for approximately 24 h. Extracts were subsequently centrifuged at 5000 rpm for 20 min. Chlorophyll-a samples were determined in a photometer Shimadzu UV-1700, and calculated as micrograms per liter.